Gastrointestinal physiology - Barrett, Kim E. (Lange Medical Books/McGraw-Hill, Medical Pub. Division, 2014)
This new title features a system- and disease-based approach to the aspects of gastrointestinal pathophysiology, essential for an understanding of clinical medicine. Bridging the gap between basic science and clinical medicine, this text provides students with a solid understanding of symptom identification and the underlying disease mechanism. Features clinical pearls, learning objectives, study questions, algorithms, and key concepts highlighting the presentation in each chapter